Enrichment of the vocabulary in the formation of the Ukrainian official anl business style (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In the article the sources of enrichment of the vocabulary are exposed in the Ukrainian official and business style in the 20–30th  years of the 20th  century . The author reasons, that  in the researched period dialectal vocabulary, archaisms and neologisms  are included to lexical composition.
Keywords: official and business style; literary norms; thematic groups of vocabulary; kancelyarizm; archaism; dialectal forms; neologism